Physical self-esteem and its relationship to some elements of physical fitness of young football players (Journal of the College of Basic Education, 2022)
The research aims to examine the relationship of the physical self-esteem of the football player with the level of physical fitness of young football players in football. The importance of the research lies in studying the impact and evaluating the physical self of young football players and studying the relationship of this level of appreciation with the real physical abilities of these young players, given the belief that there is a relationship between what the player believes in himself from the capabilities and the real reality of his physical abilities. The research community was identified with the young football players of Al-Samawa Sports Club and the participants in the Iraq Youth Clubs League for the 2020-2021 season, numbering (20 players) ranging in age from 13-15 years.The researcher has been used the descriptive approach in the correlative relations style for its suitability to the nature of the problem.